2014
DOI: 10.1152/jn.00217.2014
|View full text |Cite
|
Sign up to set email alerts
|

Vocal motor changes beyond the sensitive period for song plasticity

Abstract: Behavior is critically shaped during sensitive periods in development. Birdsong is a learned vocal behavior that undergoes dramatic plasticity during a sensitive period of sensorimotor learning. During this period, juvenile songbirds engage in vocal practice to shape their vocalizations into relatively stereotyped songs. By the time songbirds reach adulthood, their songs are relatively stable and thought to be "crystallized." Recent studies, however, highlight the potential for adult song plasticity and sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(73 citation statements)
references
References 102 publications
4
69
0
Order By: Relevance
“…This result is consistent with our data showing a significant difference in the variability of gap duration but not syllable duration between early and late adults, despite the different developmental time scales of two species. Similarly, a study on Bengalese finches has reported that younger birds (6 monthold, corresponded to young and early adult birds in our study) showed significantly greater variability in gap durations but not in syllable durations than older birds (23 month-old, corresponds to our late adult birds) (James and Sakata, 2014), consistent with the present study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is consistent with our data showing a significant difference in the variability of gap duration but not syllable duration between early and late adults, despite the different developmental time scales of two species. Similarly, a study on Bengalese finches has reported that younger birds (6 monthold, corresponded to young and early adult birds in our study) showed significantly greater variability in gap durations but not in syllable durations than older birds (23 month-old, corresponds to our late adult birds) (James and Sakata, 2014), consistent with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, we observed a tendency that target gap durations were shortened with age in NA experiments while non-target gap durations were not. Shrinkage of gap durations during development have been generally observed in previous studies (Glaze and Troyer, 2013;James and Sakata, 2014), then, it would be unclear whether the shrinkage of target gap observed here could be attributed to side effects of NA experiments.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…To analyse variation in song tempo between VD and LD song, we calculated the duration of the first motif of each song bout and analysed experimental variation in first motif durations using the same four-way factorial model as above (only first three bouts). Only the first motif in each bout was analysed for this comparison because motif durations change as bout length increases (e.g., Chi and Margoliash, 2001; Glaze and Troyer, 2006; James and Sakata, 2014; James and Sakata, 2015) and because bout lengths differed between VD and LD song (Figure 3; Table S2). There was no significant effect of any factor, including Condition, on song tempo (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%